2014
DOI: 10.1016/j.jmateco.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Rational belief hierarchies

Abstract: We consider agents whose language can only express probabilistic beliefs that attach a rational number to every event. We call these probability measures rational. We introduce the notion of a rational belief hierarchy, where the first order beliefs are described by a rational measure over the fundamental space of uncertainty, the second order beliefs are described by a rational measure over the product of the fundamental space of uncertainty and the opponent's first order rational beliefs, and so on. Then, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Henceforth, whenever we write "rational belief hierarchies" or "rational types", we implicitly refer to elements of T Q , thus omitting to explicitly say that they satisfy coherency and common certainty in coherency. Following Brandenburger and Dekel (1993), Tsakas (2013) proved the existence of a terminal type space model of rational belief hierarchies, implying that every rational belief hierarchy is identified by a Borel probability measure on Θ × T Q , via the injective function…”
Section: Rational Belief Hierarchies and Rational Typesmentioning
confidence: 99%
See 2 more Smart Citations
“…Henceforth, whenever we write "rational belief hierarchies" or "rational types", we implicitly refer to elements of T Q , thus omitting to explicitly say that they satisfy coherency and common certainty in coherency. Following Brandenburger and Dekel (1993), Tsakas (2013) proved the existence of a terminal type space model of rational belief hierarchies, implying that every rational belief hierarchy is identified by a Borel probability measure on Θ × T Q , via the injective function…”
Section: Rational Belief Hierarchies and Rational Typesmentioning
confidence: 99%
“…The latter is not surprising, as one can easily see that there exist probability measures π ∈ ∆(Θ × T Q ) with marg Θ π / ∈ ∆ Q (Θ), e.g., a measure with π({θ} × T Q ) = √ 2/2. More interestingly, Tsakas (2013) showed that there exist types that are mapped via g to nonrational probability measures over Θ × T Q . Throughout the paper, we call the rational types that do not exhibit this property universally rational, i.e., a type t ∈ T Q is universally rational if and only if g(t) ∈ ∆ Q (Θ × T Q ).…”
Section: Rational Belief Hierarchies and Rational Typesmentioning
confidence: 99%
See 1 more Smart Citation
“… It can be shown that a finite measure that takes on only rational values can take on only finitely many values; see, for example, Tsakas (2014, Proposition 1). In the present context, such a measure must have a finite support.…”
mentioning
confidence: 99%